The Development of Late‐Stage Continental Breakup: Seismic Reflection and Borehole Evidence from the Danakil Depression, Ethiopia. Issue 9 (6th September 2018) - Bastow, Ian D.; Booth, Adam D.; Corti, Giacomo; Keir, Derek; Magee, Craig; Jackson, Christopher A.‐L.; Warren, John; Wilkinson, Jason; Lascialfari, Matteo
Abstract: During continental breakup, the locus of strain shifts from a broad region of border faulting and ductile plate stretching to a narrow zone of magma intrusion in a young ocean basin. Recent studies of volcanic rifts and margins worldwide suggest this shift occurs subaerially, before the onset of seafloor spreading. We test this hypothesis using recently acquired seismic reflection and borehole data from the Danakil Depression, Ethiopia, a unique region of transition between continental rifting and seafloor spreading. Our data, located near Dallol, ~30 km northwest of the Erta'Ale Volcanic Segment, reveal a remarkably thick (>1‐km) sequence of young (~100‐ka) evaporites in a basin bound by a major (≤400‐m‐throw), east‐dipping normal fault. To generate such a large amount of subsidence in such a relatively short time, we propose that upper‐crustal extension in Danakil is currently dominated by faulting, not magmatic intrusion. Given the region's markedly thinned crust (~15‐km‐thick), relative to elsewhere in Afar where magma‐assisted rifting dominates and maintains crustal thickness at ~25 km, mechanical extension in Danakil is likely coupled with ductile extension of the lower‐crust and mantle lithosphere. Despite proximity to the voluminous lavas of the active Erta'Ale Volcanic Segment, evidence for igneous material in the upper ~2 km of the 6‐ to 10‐km‐wide basin is limited. Late‐stage stretching was likely aided by thermal/strain‐induced lithospheric weakening following protracted magma‐assisted rifting. Basin formation immediately prior to the onset of seafloor spreading may also explain the accumulation of thick marine‐seepage‐fed evaporite sequences akin to those observed, for example, along the South Atlantic rifted margins. Key Points: New seismic reflection, and borehole data from the Danakil Depression, Ethiopia, constrains late‐stage continental breakup A thick sequence of evaporites has been deposited over tens to hundreds of thousands of years in a basin bounded by a major, E‐dipping normal fault The onset of magmatic extension during continental rift development does not necessarily herald the onset of seafloor spreading